Validating the role of the MAL/SRF pathways in promoting stem-like features downstream of the P-cadherin/actin cytoskeleton complex - Meireles, Isabel Patrícia Dias (2021)
Dissertação de Mestrado em Bioquímica apresentada à Faculdade de Ciências e Tecnologia